"Globally adept citizens?": Varying conceptions of generic graduate attributes by high school career advisers. (April 2018) - Lewis, Christopher; Wilson, Rachel
Research on the conceptions of generic graduate attributes has focused on employers and higher education institutions and finds inconsistent conceptions and differing values attributed to them. Little work exists surrounding those charged with advising prospective students. Adopting phenomenographic methodology, this research establishes conceptions of generic graduate attributes held by Australian career advisers in NSW secondary schools: defining and describing two outcome spaces by which generic graduate attributes are understood. Advisers see generic graduate attributes as close to personal qualities, strongly related to employment, or important for self-development. Advisers value generic graduate attributes as "minimal" or "valid". The hierarchical nature of the categories, and dichotomy of views on valuing generic graduate attributes, demonstrate varying conceptions, ranging from simplistic to an advanced understanding surpassing those found in the policies of employers and universities. The variation suggests those charged with advising future generations do not share a common understanding of generic graduate attributes and raises critical implications for research, policy, and practice.